Mentoring in Pediatric Thoracoscopy: From Theory to Practice - Macchini, Francesco; Leva, Ernesto; Gentilino, Valerio; Morandi, Anna; Rothenberg, Steven Scot (Frontiers in Pediatrics, 2021)
Introduction: Thoracoscopy represents the most challenging area of pediatric minimally invasive surgery due to its technical difficulty. A standardized training program would be advisable. The aim of this study is to evaluate the results of our surgical training. Materials and Methods: A retrospective, single-center, cohort study was performed. The following four-step program was tested: 1. theoretical part; 2. experimental training; 3. training in centers of reference; 4. personal operative experience. Particular attention was focused on the choice of mentor. Times and modality of adherence to the program were evaluated. The effectiveness and safety of the training were evaluated according to the surgical results of esophageal atresia (EA/TEF) repair and resection of congenital lung malformations (CLM). The study was conducted from January 2014 to May 2020. Attending surgeons with previous experience in neonatal and pediatric laparoscopy were selected for the training program after being evaluated by the head of Department. Results: The training program was fully completed in 2 years. Twenty-four lobectomies, 9 sequestrectomies, 2 bronchogenic cyst resections and 20 EA/TEF repair were performed. Thoracoscopy was always feasible and effective, with no conversion. The operative times progressively decreased. Only 3 minor complications were recorded, all treated conservatively. Conclusions: a standardized training program is highly desirable to learn how to safely perform advanced pediatric thoracoscopy. The 4-steps design seems a valid educational option. The choice of the mentor is crucial. An experience-based profile for pediatric surgeons who may teach thoracoscopy is advisable.